The Pesantren Approach In Building Peace Education And Social Stability For Young Children: A Literature Review 2008-2025 - Toilatun Nafiiyah; Agik Nur Efendi; Mohammad ali Al Humaidy; Himayatul Sya’adah (Institut Agama Islam Negeri Madura, 2026)
Social conflict and intolerance in Indonesia emphasize the importance of peace education from an early age. This study aims to explore the pesantren approach in building peace education and social stability for early childhood. The study uses a qualitative method with a library research design through systematic analysis of 45 main literature sources, including indexed journal articles, reference books on Islamic education and peace education, and pesantren curriculum documents based on early childhood education. The data were analyzed using thematic content analysis techniques to identify patterns of peace value integration in pesantren educational practices. The findings show that Islamic boarding schools develop the foundations of peaceful character through three main approaches: (1) moral education based on akhlak (ethics) that instills the values of tasamuh (tolerance) and ta'awun (cooperation), (2) the halaqah tradition as a space for democratic dialogue to practice communication and conflict resolution, and (3) community-based social activities as a laboratory for practicing the values of peace. This holistic approach integrates cognitive, affective, and behavioral dimensions in character building.The practical implication of this research is the need to develop a more structured pesantren-based peace education curriculum and strengthen collaboration between pesantren and formal educational institutions to reinforce social stability in multicultural societies.